APAKAH GEREJA BERADA DI RUANG HAMPA? HATI-HATI KEHILANNGAN GENERASI MUDA - Stimson Hutagalung (Jurnal Koinonia, 2014)
Young generations are church motors.  They are often called as the strengths for today and leaders for tomorrow.  However, there is a great danger of losing the young generations that will weaken the church.  The church building may be present, but it may be empty.  The program may be held, but the effect cannot be felt.  Therefore, the church should make a movement to proctect these young generations from the negative cultures, so that the church will not lose its young generations that will be the leaders of tomorrow.